Temperature effect on the light propagation in a tapered optical fiber with a twisted nematic liquid crystal cladding - Korec, Joanna; Stasiewicz, Karol Antoni; Jaroszewicz, Leszek Roman (Photonics Letters of Poland, 2019)
This paper presents the influence of temperature on optical power spectrum propagated in a tapered optical fiber with twisted nematic liquid crystal cladding (TOF-TNLCC) modulated by an electric field. The measurements were performed for a liquid crystal cell with the twisted orientation of ITO layers, filled with E7 mixture. The induced reorientation of liquid crystal (LC) n-director was measured for visible and near-infrared wavelength range [550-1100 nm] at the electric field range of 0–160 V and temperature range of 20-60 °C. The relation between temperature and the optical power spectrum of the investigated device has been established. Full Text: PDF References V.J. Tekippe, "Passive fiber optic components made by the fused biconical taper process", Proc. SPIE 1085 (1990). CrossRef T. A. Birks, Y. W. Li, The shape of fiber tapers, Journal of Lightwave Technology 10, 4 (1992). CrossRef J. Korec, K. A. Stasiewicz, O. Strzeżysz, P. Kula, L. R. Jaroszewicz, Electro-Steering Tapered Fiber-Optic Device with Liquid Crystal Cladding, Journal of Sensors 2019: 1-11 (2019) CrossRef Ch. Veilleux, J. Lapierre, J. Bures, Liquid-crystal-clad tapered fibers, Opt. Lett. 11, 733-735 (1986) CrossRef J. F Henninot, D. Louvergneaux, N. Tabiryan, M. Warenghem, Controlled leakage of a tapered optical fiber with liquid crystal cladding, Molecular Crystals and Liquid Crystals, 282, 297-308. (1996). CrossRef Y. Wang, et.al., Tapered optical fiber waveguide coupling to whispering gallery modes of liquid crystal microdroplet for thermal sensing application, Opt. Express 25, 918-926 (2017) CrossRef J. Korec, K. A. Stasiewicz, O. Strzeżysz, P. Kula, L. R. Jaroszewicz, . E. Moś, Tapered fibre liquid crystal optical device, Proc. SPIE 10681 (2018) CrossRef G. Assanto, A. Picardi, R. Barboza, A. Alberucci, Electro-optic steering of Nematicons, Phot. Lett. Poland 4, 1 (2012). CrossRef A.Ghanadzadeh Gilani, M.S. Beevers, The Electro-optical kerr effect in eutectic nematic mixtures of E7 and E8,J ournal of Molecular Liquids, 92, 3 (2001). CrossRef E. C. Mägi, P. Steinvurzel, and B.J. Eggleton, Tapered photonic crystal fibers, Opt. Express 784, 12, 5 (2004). CrossRef Y. Li and J. Lit, Transmission properties of a multimode optical-fiber taper, J. Opt. Soc. Am. A 2, (1985). CrossRef J. Korec, K. A. Stasiewicz, and L. R. Jaroszewicz, Temperature influence on optical power spectrum of the tapered fiber device with a liquid crystal cladding, Proc. SPIE 11045, 110450I (2019) CrossRef L.M. Blinov, Liquid crystals: physical properties and their possibilities in application, Advances in Liquid Crystal Research and Applications, (1981). CrossRef